(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Speech goes in the article about the features of the use of terms in poetic works of Lina Kostenko. Certainly, that terms in the poetry of Lina Kostenko represent scientific and technical progress, knowledge of lyric heroine with modern technologies, come forward as logicaly- semantic focis of different sort of metaphorical constructions.